Tell me how good I am - An Empirical Investigation of Peer Feedback in IT-based Innovation Contests - Haller, Jörg; Adamczyk, Sabrina; Bansemir, Bastian; Bullinger-Hoffmann, Angelika; Möslein, Kathrin (International Product Development Conference (IPDMC), 2011)
Open innovation activities particularly rely on interactions between participants which are increasingly accomplished on IT-based platforms and facilitated by means of commenting functionalities. While there are first studies on the content and use of comments on open innovation platforms, this study extends previous research by examining the impact of cognitive and affective feedback by other participants on the degree of creativity of submissions. We apply a quasi-experimental approach to an IT-based innovation contest and find that cognitive feedback as well as the combination of both cognitive and affective feedback positively impacts the degree of creativity of submissions. Our findings hold important implications for the facilitation of open innovation activities. If a high degree of creativity is required, organizers should implement cognitive and affective feedback by means of technical functionalities as well as human interaction with participants.
WiSo-Import:2015-04-17:555
Keywords: Innovation